Rice Paddy Soil Seedbanks Composition in a Mediterranean Wetland and the Influence of Winter Flooding - José M. Osca; Felip Galán; Héctor Moreno-Ramón (Agronomy, 2021)
Soil seedbanks are defined in composition and quantity by many environmental factors inherent to a specific area, and they can be an indicator of the potential problems of weeds in crops. In Valencia (Spain), rice is cultivated with continuous flooding during the growing season, and after harvesting, many of the paddy fields are flooded again during the winter. This study investigates the paddy fields’ soil seedbank composition in this Mediterranean paddy area and the effect of winter flooding on the soil seedbank. Multispectral images from the Sentinel-2 satellite were used to characterise the water level of paddies in winter. Satellite images facilitated the characterisation of winter flooding in fields. Soil samples from sixty-nine points distributed over 15,000 ha of paddies were used to determine the composition of the seedbank plots. The data were spatially represented by geographic information systems. The species that contributed most to the paddy seedbank were Cyperus difformis L., an important rice weed in the Mediterranean area, and other rice weeds such as Echinochloa sp. and Leptochloa fusca subspecies. Other species with a great contribution to the seedbank are species that develop in paddy fields that produce a large quantity of small seeds, such as Lemna sp., Polypogon monspeliensis (L.) Desf., and Nasturtium officinale R. Br. These species interfere little or do not interfere with the rice crop. The study revealed that in general, flooding reduced seedbank density with differences between species. Furthermore, the influence of winter flooding on the different plant species obtained as well as their distribution maps are a further step in this protected area from the point of view of weed management in rice crop, as well as in the management of this Mediterranean wetland.